Handling of diabetic foot in Type 2 Diabetes Mellitus (T2DM) patients based on a vascular approach: a literature review - Niko Azhari Hidayat; Abed Nego Okthara Sebayang (Surgical Residency Program Syiah Kuala University, 2021)
Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia that occurs due to insulin disorders, insulin action, or a combination of both. Based on data from the 2014 IDF, Indonesia ranks 5th in the world of patients with DM. Diabetic foot is one of the chronic complications of DM that is often encountered. Early vascular assessment in the legs of a diabetic patient is recommended to reduce mortality and morbidity. The vascular examination begins with a capillary refilling examination, palpation of the lower extremity arteries, and a further ankle-brachial index assessment. The vascular approach aims to assess the vascularization of the diabetic foot is still good or has experienced occlusion or obstruction due to inadequate blood vessels. Diabetic foot care is based on the classification recommended by the International Working Group On Diabetic Foot. Management of diabetic foot involves a variety of multidisciplinary, one of them with a vascular approach. The vascular approach also aims to determine the appropriate therapy for the diabetic foot. This study aims to provide better understanding